PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, ASIMETRI INFORMASI DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Sari Nofita Sari; Enni Savitri; Mela Fito Nanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to analyze the effect of managerial ownership onearnings management, the effect of institutional ownership on earningsmanagement, the effect of firm size on earnings management, the effect ofinformation asymmetry on earnings management and the effect of profitability onearnings management. The population use in this study is 132 manufacturingcompany listed in Indonesia Stock Exchnage in 2012-2016. while sample in thisresearch amount to 15 companies manufacturing. Sampling technique in thisresearch using purposive sampling technique and analysis teqhnique usingmultiple liniear regression The result of this research indicate that managerialownership and profitability influences on earnings management while theinstitutional ownership, information asymmetry has no effect on earningsmanagement.Keywords : GCG, Managerial Ownership, Institutional Ownership, Firm Size,Information Asymmetry, Profitability, Earnings Management.